Prevalence of temporomandibular joint disorder symptoms in Cibodas Maribaya Village Bandung District - Kurnikasari, Erna (Padjadjaran Journal of Dentistry, 2010)
Temporomandibular joint disorder is a stomatognathic system disorder causing mandibular function disturbance that clinically shows the following symptoms: clicking, crepitation, limited mouth opening, pain in masticatory muscles, pain in the jaw area, deviated mouth opening, ringing ear, pain around ear area, and headache. Experts stated that the prevalence of joint disorder was high. A study was conducted to the people of Cibodas Maribaya Village Bandung District who came to the Community Work event with results showing that the prevalence of clicking was 34 people or 32.4%, the deviation was found in 36 people or 34.3%, muscle pain was found in 28 people or 26.7%, a headache was found in 35 people or 33.3%, ear disorders was found in 23 people or 21.9%.